Socialization factors in the counselors' professional attitudes and role orientation - Lolarga, Erlinda (Garcia) 1929-
This study investigates the hypothesized relationships between adult socialization indicators. It involves the length and type of educational training for professional socialization; length of employment, hierarchical position and educational level of work for organizational socialization; five attitudinal components of professionalization and two types of role orientation identified as professional and bureaucratic.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Keywords: Counseling; Social case work; Socialization